Structural characterization of a tin oxyhydroxide gel and its precursor sol - Vollet, D. R. [UNESP]; Hiratsuka, R. S. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Craievich, A. F. (Elsevier, 1992)
The structures of a tin oxyhydroxide colloidal gel and that of its precursor sol were studied by small-angle X-ray scattering. The experimental data were analyzed on the basis of a structural model of fractal geometry. The gel is concluded to be a mass fractal which is a modification of the fractal structure of the aggregates in the precursor sol. © 1992 Elsevier Science Publishers B.V. All rights reserved.
Keywords: Sols; Tin Compounds; X-Ray Analysis; Fractal Geometry; Fractal Structure; Small Angle X-Ray Scattering; Structural Characterization; Tin Oxyhydroxide Gel; Gels